Market potential of Cavendish banana in five major importing countries of the Philippines using seemingly unrelated regression - Alba, Kriza Kye A.
Market potential of Cavendish banana in five major importing countries of the Philippines were estimated using Ordinary Least Square (OLS) and Seemingly Unrelated Regression (SUR) models. Secondary aggregate time-series data of each country and were used. The resulting OLS and SUR model for Cavendish banana in major importing countries-Japan, Saudi Arabia, China, Korea and Hongkong-suggests that contemporaneous correlation does not exits which mean that OLS result is better than the result obtained in SUR. The import price in Japan and China are significant with negative coefficient that conforms to the theory. It implies that for every unit increase on import price, import demand will decrease. The demand elasticity of the Cavendish banana showed that China is the most sensitive to price changes because it has the highest own-price elasticity. Futhermore, orange from USA is proved to be a substitute and Cavendish banana from Ecuador is also a strong competitor to Cavendish banana in Philippines, but a complementary product in Japan. Market potential, on the other hand, is observed in China because it has significant income elasticity that is greater than one. In this manner, import demand in China is sensitive to the income changes. Moreover, since three out of five countries exhibited a substitute relationship between Cavendish banana and orange, the industry must create strategies in order to cope up with the increasing competition. The industry may considerably take into considerations its pricing strategies and demand of the product in the importing countries. Thus, given the results obtained from the study, the government should implement policy makers and support system to the industry to meet the quality and demand of the export market. Moreover, the exporting country has also the potential to expand new markets in producing Cavendish banana to other countries.